Digital Marketing, Digital Finance, and Electronic Payment Systems as Drivers of SME Financial Performance: A Conceptual Framework for Emerging Economies - Mustapha Badamasi; Kabiru Tsoho (Jurnal Inovasi Bisnis dan Kewirausahaan, 2026)
This conceptual paper investigates the unique theoretical connections between the adoption of digital technologies, namely digital marketing, digital finance, and electronic payment systems, and the financial performance of Small and Medium Enterprises (SMEs) in emerging economies, particularly within the Nigerian context. While empirical research frequently treats digital transformation as a singular entity, this paper employs a multi-theoretical framework, incorporating the Technology Acceptance Model (TAM), Resource-Based View (RBV), and Diffusion of Innovation (DOI) Theory, to analyze the specific value contributions of various digital tools. The study formulates a detailed conceptual framework and puts forth a series of theoretical propositions, contending that digital finance improves capital liquidity, digital marketing facilitates market growth through network effects, and electronic payment systems minimize transaction friction. The proposed framework serves as a guide for future researchers to empirically validate these distinct pathways and offers policymakers a theoretical foundation for targeted interventions in digital infrastructure.